Study on the relationship between service quality and customer satisfaction among Sport Center users in University Utara Malaysia - Nur Fatihah, Husin (2018)
The purpose of this study is to study the relationship between service quality and customer satisfaction among the users of the Sports Center in University Utara Malaysia. The respondents of this study are the UUM students who are using the services in the Sports Center. The factors investigated in this study are five dimensions of service quality which is tangible, responsiveness, reliability, assurance and empathy. Thus, the objectives of this research paper are: (a) To investigate the relationship between tangibility and the student's satisfaction. (b) To identify the relationship between reliability and the student's satisfaction. (c) To determine the relationship between responsiveness and the student's satisfaction. (d) To examine the relationship between assurance and the student's satisfaction. (e) To identify the relationship between empathy and the student's satisfaction. (f) To determine the relationship between overall service quality and the student's satisfaction. In this study, the quantitative method was implemented. 1138 students as the population and 297 students are chosen as a sample size. In assessing the relationship between variables, a total of 297 questionnaires were distributed and analyzed using SPSS 24.0 to produce an accurate finding. Correlation analyses were used to answer the research hypothesis. The findings of the research proves that service quality is significantly related to the student's satisfaction. This study clearly illustrate that tangibility and empathy have the most influence towards increasing the student's satisfaction. This study also contributes to a new scope of research in the business field and discusses the implications, recommendations for future research and a summary of the study as well.